Transcutaneous Electrical Nerve Stimulation at the Acupuncture Points to Relieve Pain of Patients Under Mechanical Ventilation: A Randomized Controlled Study - Javad AminiSaman; Saeed Mohammadi; HasanAli Karimpour; Behzad Hemmatpour; Hengameh Sharifi; Rasool Kawyannejad (Medical Association of Pharmacopuncture Institute, 2018)
Background and objective: Electrical stimulation and acupuncture points as nonpharmacological methods have been the focus of pain reduction in different patients. This study is aimed at determining the effects of transcutaneous electrical nerve stimulation (TENS) on the acupuncture points of pain in patients under mechanical ventilators. Materials and methods: This randomized double-blind clinical trial study was conducted on 50 patients undergoing mechanical ventilation in intensive care units of Imam Reza hospital in Kermanshah, Iran, in 2017. The patients were randomly allocated into intervention and placebo groups. In the intervention group, TENS electrodes were placed on points Hegu and Zusanli. Pain severity was measured using the Care Pain Observation Tool scale, and the dosages of narcotics and sedation intake were recorded. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) software, version 19. Results: The level of pain in patients decreased in the intervention group in comparison with the sham group, and this decline was significant during certain hours (p < 0.05). The amount of analgesic and sedation drugs used was less significant in the intervention group than in the sham group (p = 0.01; p = 0.04). Conclusion: The results showed that the use of TENS on acupuncture points can decrease the level of pain and opioid consumption in intubated patients under a mechanical ventilator. Keywords: acupuncture, Hegu, intensive care unit, pain management, Zusanli